Anti-inflammatory effect of euphane- and tirucallane-type triterpenes isolated from the traditional herb Euphorbia neriifolia L - Chang, Stephen S.; Huang, Hung-Tse; Wei, Wen-Chi; Lo, I-Wen; Lin, Yu-Chi; Chao, Chih-Hua; Liao, Geng-You; Shen, Yuh-Chiang; Chen, Jih-Jung; Li, Tsung-Lin; Lin, Liang-Tzung; Tai, Chen-Jei; et al. (Frontiers in Chemistry, 2023)
The Euphorbiaceae plant Euphorbia neriifolia L. is distributed widely in India, Thailand, Southeastern China, and Taiwan and used as a carminative and expectorant to treat several inflammation-related diseases, such as gonorrhoea, asthma, and cancer. In the course of our search for potential anti-inflammatory agents from the titled plant, 11 triterpenes from the stem of E. neriifolia were isolated and reported in our previous endeavor. Given its rich abundance in triterpenoids, the ethanolic extract in this follow-up exploration has led to the isolation of additional eight triterpenes, including six new euphanes—neritriterpenols H and J–N (1 and 3–7)—one new tirucallane, neritriterpenol I (2), and a known compound, 11-oxo-kansenonol (8). Their chemical structures were elucidated on the basis of spectroscopic data, including 1D- and 2D NMR, and HRESIMS spectra. The absolute stereochemistry of neritriterpenols was determined by single-crystal X-ray diffraction analysis, ICD spectra, and DP4+ NMR data calculations. Compounds 1–8 were also evaluated for their anti-inflammatory activity by using lipopolysaccharide (LPS)-stimulated IL-6 and TNF-α on RAW 264.7 macrophage cells. Intriguingly, the euphane-type triterpenes (1 and 3–8) showed an inhibitory effect on LPS-induced IL-6 but not on TNF-α, while tirucallane-type triterpene 2 showed strong inhibition on both IL-6 and TNF-α.